The Effect of Teacher Competence and Students Motivation in Adventist Junior Hight School Olobaru, Parigi Mautong Regency: Pengaruh Kompetensi Guru dan Motivasi Belajar Siswa SMP Advent Olobaru Kabupaten Parigi Mautong - Julita Inggrinne Nelwan; Cornelia Timpal; James Edward Lalira (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In addition to a well-organised system or management, learning also requires qualified teachers, namely teachers who are able to display student learning motivation in carrying out their duties and obligations professionally. As a form of scientific accountability, this research seeks to reveal the effect of teacher competence on student learning motivation, a spirit that must exist between the two parties to improve the quality of education. Armed with the use of quantitative research methods as a work reference, the researchers selected teachers and students at Adventist Junior High School Olobaru, Parigi Moutong Regency as population and samples. Observations, interviews and questionnaires were prepared as tools to collect data, while Sugiono's (2014) simple linear regression form served as the data analysis technique. Based on the results of the analysis, it was found that teacher competence has a positive and significant influence on student learning motivation. This proves that improving teacher competence will also improve the quality of education nationally.